PATH ANALYSIS OF MONETARY POLICY MECHANISMS: DOES ECONOMIC CAPACITY MEDIATE PRICES? - MG Westri Kekalih Susilowati; Retno Yustini Wahyuningdyah (Jurnal Penelitian Ekonomi dan Bisnis, 2020)
The single objective of Bank Indonesia is Rupiah's stability. Within the monetary policy framework, the monetary instruments affect the operational targets (money supply and interest rates). Those operational targets effect rupiah stability troughs its effect on economic capacity/GDP.  Using 108 monthly data, that is analyzed by path analysis; this study discusses the effect of net foreign assets (NFA) and net domestic assets (NDA,) and interest rates on the prices (CPI) through their effects GDP. The results show that NFA and NDA have a significant positive effect on GDP, while interest rates are tended to be negative. However, neither the NFA nor the NDA has been proven to have a direct significant effect on CPI. The interest rate has been proven to have a direct significant effect on CPI. GDP was not proven to have a significant effect on the CPI and neither mediates the effects of operational targets on CPI.Keywords: Rupiah; Prices; CPI; Stability; Money